Price Transmission and Marketing Efficiency of Mustard Greens in Grinting Village, Tulangan District - Amirah Afifah; Sri Widayanti; Ika Sari Tondang (Universitas Medan Area, 2026)
Price differences of mustard greens between the farm level and the final consumer indicate problems in price transmission and marketing efficiency. This study aims to analyze the elasticity of price transmission and the level of marketing efficiency of mustard greens in Grinting Village. The research was conducted using a survey method involving farmers and marketing institutions, with data analysis covering the identification of marketing channels, marketing margins, farmer’s share, price transmission elasticity, and the Marketing Efficiency Index (MEI). The results show that there are four marketing channels for mustard greens with different characteristics and levels of efficiency. The price transmission elasticity indicates that price changes at the consumer level are not fully transmitted to the farm level. Longer marketing channels tend to generate higher marketing margins and lower farmer’s share. In contrast, the shortest marketing channel, in which farmers sell directly to consumers, is the most efficient channel as it provides a higher price proportion to farmers. These findings highlight the importance of developing shorter marketing channels to improve the welfare of mustard green farmers.